Importance of phenols structure on their activity as antinitrosating agents: A kinetic study - Marcia Pessego; Ana M Rosa da Costa; Jose A Moreira (Wolters Kluwer Medknow Publications, 2011)
Objective : Nitrosative deamination of DNA bases induced by reaction with reactive nitrogen species (RNS) has been pointed out as a probable cause of mutagenesis. (Poly)phenols, present in many food items from the Mediterranean diet, are believed to possess antinitrosating properties due to their RNS scavenging ability, which seems to be related to their structure. It has been suggested that phenolic compounds will react with the above-mentioned species more rapidly than most amino compounds, thus preventing direct nitrosation of the DNA bases and their transnitrosation from endogenous N-nitroso compounds, or most likely from the transient N-nitrosocompounds formed in vivo. Materials and Methods : In order to prove that assumption, a kinetic study of the nitroso group transfer from a N-methyl-N-nitrosobenzenesulfonamide (N-methyl-N-nitroso-4-methylbenzenesulfonamide, MeNMBS) to the DNA bases bearing an amine group and to a series of phenols was carried out. In the transnitrosation of phenols, the formation of nitrosophenol was monitored by Ultraviolet (UV) / Visible spectroscopy, and in the reactions of the DNA bases, the consumption of MeNMBS was followed by high performance liquid chromatography (HPLC). Results : The results obtained point to the transnitrosation of DNA bases being negligible, as well as that of phenols bearing electron-withdrawing groups. Phenols with methoxy substituents in positions 2, 4, and / or 6, although they seemed to react, did not afford the expected product. Phenols with electron-releasing substituents, unless these blocked the oxygen atom, reacted with our model compound at an appreciable rate. O-nitrosation of the phenolate ion followed by rearrangement of the C-nitrosophenol seemed to be involved. Conclusion : This study provided evidence that the above compounds might actually act as antinitrosating agents in vivo.